مصادر القانون الدولي للمجاري المائية الدولية - الجوهر, الدالع (University of Eloued جامعة الوادي, 2020)
حظيت الأنهار الدولية بمنظومة قانونية مؤطرة لكيفية انتفاع الدول بمياهها حيث تراوحت مصادر قواعدها إلى مصادر رسمية وأخرى احتياطية، فالمصادر الرسمية تمثلت في المعاهدات الدولية ، ثم يليها العرف، اضافة إلى هذه المصادر المبادئ العامة للقانون كمصدر رسمي ثالث ، أما المصادر الإحتياطية التي يلجأ إليها القاضي إذا لم تسعفه المصادر الرسمية في الفصل في النزاع المعروض عليه هي أحكام القضاء المصدر الإستدلالي الأول المنشئ للقواعد القانونية المنظمة لإستغلال المجاري المائية، فضلا عن ذلك فإن آراء الفقهاء يعد المصدر الإحتياطي الثاني، وفي الأخير تعد مبادئ العدل والإنصاف مصدرا من المصادر الإحتياطية للقانون الدولي للأنهار. International rivers have benefited from a legal system framed for the way countries would utilize their waters. This system’s rules vary between official and provisional rules.The official sources are represented by international treaties, customs and the general principles of law. The provisional sources, to which the judge may have recourse in case the official ones fail to solve the dispute that is assigned to him, are judgements – the first constructive source that builds up the legal rules setting the exploitation of waterways. Furthermore, the jurists’ opinions are considered as the second provisional source. The principles of justice and fairness are considered as one of the different provisional sources of the international law of rivers.
مجلد11، عدد2
Keywords: الأنهار الدؤلية ; المجاري المائية الدؤلية ; النزاعات; internationational rivers ; international waternational ; conflits